Efektivitas Pupuk Organik Cair dengan Bioaktivator B-8 dalam Meningkatkan Pertumbuhan Sorgum (Sorghum bicolor) - Nur'aini Nur'aini (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
Sorghum (Sorghum bicolor) is a vital cereal crop known for its resilience in arid and semi-arid regions, making it an essential crop for food security. However, its growth and productivity are significantly affected by soil fertility and nutrient management. This study aimed to evaluate the effectiveness of liquid organic fertilizer (LOF) enriched with the B-8 bioactivator in improving sorghum growth. The experiment utilized a randomized complete block design (RCBD) with five treatments: LOF dilutions of 1:10 (P1), 1:30 (P2), 1:50 (P3), 1:80 (P4), and 1:100 (P5), alongside a control group (P0) without any fertilizer. Each treatment was replicated five times, and plants were monitored for growth parameters such as plant height, stem diameter, and number of leaves, with measurements taken every three days over a 6-week period. Results indicated that the P1 treatment (1:10 dilution) consistently exhibited the highest growth performance across all parameters, reaching a maximum height of 24 cm. The P5 treatment (1:100 dilution) also showed substantial growth, though not as pronounced as P1. In contrast, the control group (P0) showed the lowest growth. These findings suggest that LOF with B-8 bioactivator can significantly enhance sorghum growth, offering a sustainable and eco-friendly alternative to chemical fertilizers for improving crop productivity.